An end-fire low profile patch antenna to work on WiMAX frequencies used for harvesting power supply - Anwer Sabah Mekki; Siba Monther Yousif; Bashar Mudhafar Ahmed; Mustafa Mohammed Jawad (Institute of Advanced Engineering and Science, 2021)
In this paper, an end-fire microstrip patch antenna (MPA) is proposed of 3 GHz as a center frequency, designed, simulated, and measured to work on WiMAX frequencies within standard of 802.16e (WiMAX). A high gain ranged between (12.117-13.324) dB, high front to back ratio (F/B) of (35.770) at the center frequency, a wide band of 1.701 GHz, low profile, and semi-ideal voltage standing wave ratio (VSWR) of 1.053 is achieved. The simulation is done using computer simulation technology (CST-MW). The proposed design is based on two Fire-retardant substrates (FR-4) of relative permittivity (ε) 4.3+j0.025 and 1.53 mm thickness for each one, which is considered a high loss material. The measurement results show good agreement with the simulated results. In addition, the design can be used for harvesting power supply from mobile towers. Finally, the proposed design is compared with two other designs in terms of power conversion efficiency and overall size.